An Overview of Macrophytes in The Tropical Wetland Ecosystem - Muzzalifah Abd Hamid; Siti Norasikin Ismail; Mashhor Mansor (Indonesian Journal of Limnology, 2021)
Macrophytes are plants that adapted to wet environment and easily be found all over the world. Macrophytes have structures that are more complex, interdependent and physically substantial; make them one of the important components of rivers, lakes and any other wetland ecosystems. Macrophytes can be categorized into four different types; emergent, floating-leaved, submerged and free-floating plants based on their structure and life form. Light, water current and wind flow are among the most important limiting factors of macrophytes occurrence in the water system. Environmental conditions such as lotic and lentic environment influence the limiting factors and would be the key for successful macrophytes distribution. Each macrophyte species could respond differently to different environmental circumstances. It also has been widely used as subject for biological indicator of ecosystem health. This paper aimed to describe the general environmental condition for macrophytes distribution, discuss their role and impact of excessive growth.